Penerapan Akuntansi Sederhana pada UMKM untuk Meningkatkan Transparansi dan Akurasi Laporan Keuangan - Risma Yunita; Anggi Rahmawati; Sabrina Harum Insani; Shafina Marita Fatisya; Luciano Deandra (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the implementation of simple accounting in Micro, Small, and Medium Enterprises (MSMEs) to improve the transparency and accuracy of financial reports. Using a descriptive qualitative approach through the literature study method, this research examines various scientific sources and previous studies relevant to the topic. Simple accounting is a recording system designed to help small business owners manage their finances regularly without requiring complex technical skills. The results of the study show that most MSME owners have carried out financial recording, but not yet in accordance with proper and systematic accounting principles. This condition causes financial reports to often be inaccurate and difficult to account for. Through the application of simple accounting, MSMEs can improve the regularity of transaction recording, separate personal and business finances, and produce more transparent, accurate, and credible financial reports. In addition, the implementation of this system helps business owners gain trust from financial institutions, facilitates access to funding, and enhances business professionalism. Therefore, simple accounting functions not only as a recording tool but also as a strategic instrument to strengthen governance and ensure the sustainability of MSMEs in Indonesia.